Can targeted job-information for adults with spinal cord dysfunction be effectively delivered online? A pilot study. (2nd January 2019) - Dorstyn, Diana; Roberts, Rachel; Murphy, Gregory; Kneebone, Ian; Craig, Ashley; Chur-Hansen, Anna; Migliorini, Christine; Potter, Elizabeth; Marshall, Ruth; Clark, Jillian; Neeson, Sharron; Stewart, Peter
Abstract : Objective : To pilot a novel email-based information package ( Work and SCI ) for job-seekers with an acquired spinal cord injury (SCI) or spinal cord dysfunction (SCI/D). Study design : Prospective, non-randomized, repeated measures trial. Setting : Community dwelling cohort in Australia. Participants : Five people with SCI (mean age 46.4 years, SD = 10.2; 4 female) initially reviewed Work and SCI . Twenty-four with SCI/D subsequently enrolled, of whom 16 (mean age 46.4 years, SD = 11.1; 7 female), completed the intervention. Intervention : Intervention participants accessed Work and SCI over a 4-week period. Outcome measures : Individual changes in pre-post scores for the My Vocational Situation Scale, Job Procurement Self-Efficacy Scale, Patient Health Questionnaire-9 and Life Orientation Test-Revised were examined. Results : Reliable change in pre-post scores across outcomes were reported by 38% ( n  = 6) of participants. Favorable comments on the Work and SCI resource were provided in addition to suggestions for improvement. Conclusions : Preliminary data suggest that Work and SCI may help to establish vocational interests among job-seekers with a SCI/D, however further work is needed to enhance participant compliance. This might include moderator support to promote and maintain participation. A controlled design will also help to identify factors that influence engagement with the Work and SCI resource.